Private education in Argentina and Brazil - Almeida, Ana Maria F. (2017)
Exploring the concept of segmentation, this article demonstrates how the expansion of the Argentinian and Brazilian school systems has been associated to processes of school differentiation that have contributed to the production and reproduction of educational inequalities. Based on the analysis of historical statistics on literacy and school enrollment as well as of documents that register the school transformations since the end of the 1800s, the article shows, first, that in both school systems, segmentation processes were and are based on the separation between public and private education rather than on differentiation of public schools curriculum. It shows also that while this type of segmentation is quite recent in Argentina, it is an old feature of the Brazilian school system. Finally, the article documents a progressive convergence between the two systems, as the private schools still offer a reserved space for the schooling of the Brazilian privileged groups and has increasingly played this role in Argentina in the last decades.